After the protests are heard : enacting civic engagement and social transformation - Welch, Sharon D. (Religion and social transformation., 2019)
From the Women's March in D.C. to #BlackLivesMatter rallies across the country, there has been a rising wave of protests and social activism. Yet, the struggle for social justice continues long after the posters and megaphones have been packed away. After the protests are heard, how can we continue to work toward lasting change?